1993
DOI: 10.1073/pnas.90.13.6270
|View full text |Cite
|
Sign up to set email alerts
|

A familial hypertrophic cardiomyopathy locus maps to chromosome 15q2.

Abstract: We report that a gene responsible for familial hypertrophic cardiomyopathy (FHC) in a kindred with a mild degree of cardiac hypertrophy maps to chromosome 15q2. The gene encoding cardiac actin, located on chromosome 15q, was analyzed and excluded as a candidate for FHC at this locus. Two additional familes with typical FHC were studied and the disorder in one aiso maps to the chromosome 15q2 locus. The maximum combined multipoint logarithm of odds score in the two linked families is 6.02. Although these two ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(37 citation statements)
references
References 13 publications
3
33
0
1
Order By: Relevance
“…Our result above is consistent with these. Thierfelder et aL (1993) mapped the familial hypertrophic cardiomyopathy locus to chromosome 15q2 and demonstrated that the cardiac actin gene is not there, with which our result is also in a good agreement.…”
supporting
confidence: 80%
“…Our result above is consistent with these. Thierfelder et aL (1993) mapped the familial hypertrophic cardiomyopathy locus to chromosome 15q2 and demonstrated that the cardiac actin gene is not there, with which our result is also in a good agreement.…”
supporting
confidence: 80%
“…The disease is often associated with disabling symptoms (angina, dyspnea, palpitations, and syncope) and is the most common cause of sudden death in otherwise healthy young individuals (2)(3)(4). HCM is genetically heterogeneous (5)(6)(7)(8)(9)(10)(11)(12)(13). The phenotype in HCM may be caused by one of several disease genes (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…HCM is genetically heterogeneous (5)(6)(7)(8)(9)(10)(11)(12)(13). The phenotype in HCM may be caused by one of several disease genes (5)(6)(7)(8)(9)(10)(11)(12)(13). In about a third of HCM kindreds, the disease is caused by 1 of at least 30 distinct mutations in the /-myosin heavy chain (f3-MHC) gene located on chromosome 14 (5,6,9,10,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, genetic heterogeneity has as well as other markers in the same region (corresponding to loci D14S71, D14S76, D14S61, and been found by molecular genetic studies in other myocardial disorders. In familial hypertrophic cardiomyop-D14S74) yield clearly negative lod scores (incidentally, the latter group of markers was also negative even in athy, mutations in chromosomes 1q3 (cardiac troponin T gene) (Watkins et al, 1993;Thierfelder et al, 1994), the study of Rampazzo et al, 1994).…”
Section: Linkage Of Arvd To 14q12-q22mentioning
confidence: 99%
“…All polymorphisms were scored without knowlmajor and minor criteria were considered: the diagnosis of ARVD edge of phenotypic data and by two independent observers. Twodepended on the presence of two major criteria from different diagpoint and multipoint lod scores were calculated using the LINKAGE nostic groups, of one major plus two minor criteria, or of four minor software package Version 5.2 (Lathrop et al, 1984; Lathrop and Lacriteria. The clinical status of the affected and unaffected relatives louel, 1985) on a SUN SPARC Server 10-401 computer.…”
Section: Introductionmentioning
confidence: 99%